Pemahaman Tahapan Pra Kontraktual Dalam Penyusunan Kontrak Untuk Mewujudkan Pelindungan Para Pihak - Agus Suwandono (Institut Teknologi dan Bisnis Semarang, 2024)
The preparation of a contract goes through several stages, ranging from pre-contractual, contractual, and post-contractual. The pre-contractual stage plays an essential role in the preparation of the contract so that the parties must understand it to minimize disputes in a contract. This community service is done through legal counselling, which begins with material delivery and a question-and-answer discussion session. The results of community service show that in the pre-contractual stage, several things need to be done, including a review of laws and regulations and legal aspects related to contracts, legal audits, business, social and technical studies, negotiations, and making a Memorandum of Understanding. This legal counselling has increased public understanding of the pre-contractual stages in contract drafting to realize the protection of the parties.